PERAN PEREMPUAN DALAM MERAWAT EKSISTENSI MANGNGAJI TUDANG SEBAGAI BAGIAN INTEGRAL PENGEMBANGAN PENDIDIKAN ISLAM DI DESA BONDE POLEWALI MANDAR (STUDI BIOGRAFI ANNANGGURU HUDAEDAH) - Abu Muslim (EDUCANDUM, 2017)
This research is a descriptive biography with a qualitative approach. This researchrequire stracing the memoir of women clerics reviewing religious patterns carried byfocusing on the function and role of the clergy in society. The study was conducted inPolewali Mandar, West Sulawesi with the focus of writing the biography of a femalecleric (annangguru) named Hudaedah (Annangguru Edda') is concerned with theteaching of the yellow book (mangngaji kittak) at Bonde village in CampalagianDistrict. Annangguru Edda' which although not having the opportunity to havequalified education is a humble figure and a role model of religious knowledge.Among the extremely popularis its ability to teach science to the public “NahwuSharaf”. The process of knowledge transfer using “Manggaji kittak” pattern is doneoutside the boarding management model Mangngaji tudang done at annangguru’shome